Evolution of Department Chairs – Analysis of Academic Chairperson’s Conference Proceedings - David Line Dr; Stephen F Pyle (Academic Chairpersons Conference Proceedings, 2018)
The Academic Chairperson’s Conference has been provided guidance to chairs for 34 years. Coding of titles and descriptions of presentations given at the first 34 ACCs provides trends in topics which are of interest to chairs. This session explores continual themes, cyclical topics, resolved issues, and emerging trends.
Keywords: Analysis; ACC-Topics; Chairperson; Trends; Issues